THE INFLUENCE OF OCCUPATIONAL SAFETY, OCCUPATIONAL HEALTH AND PHYSICAL WORKING ENVIRONMENT ON PRODUCTIVITY PALM FACTORY (PKS) WORK PROCESSING SECTION AT PT. PLANTATION NUSANTARA I COT GIREK NORTH ACEH EMPLOYEE - Alya Rehana; Yanita; Khairawati; Likdanawati (RADJA PUBLIKA, 2024)
This research aims to examine work safety, work health and the physical work environment on work productivity at the Palm Oil Factory (PKS) Processing Section at PT. Perkebunan Nusantara I Cot Girek North Aceh. The data in this research uses a questionnaire as a data collection instrument. This research uses a quantitative approach with multiple linear regression analysis and is processed using the SPSS (Statistical Package for the Social Sciences) tool. The technique taken in this research is using a saturated sampling technique as a determinant of the sample. The population taken in this research was 65 respondents from palm oil mill employees in the processing section at PT. Perkebunan Nusantara I Cot Girek North Aceh. The results of this research are that work safety partially has a positive and significant effect on the work productivity of palm oil factory employees in the processing section at PT. Perkebunan Nusantara I Cot Girek Aceh Utara, occupational health partially and significantly influences the work productivity of palm oil factory employees in the processing section at PT. Perkebunan Nusantara I Cot Girek Aceh Utara, the physical work environment partially has a positive and significant effect on the work productivity of palm oil mill employees in the processing section at PT. Perkebunan Nusantara I Cot Girek North Aceh.